Analisis Transformasi Digital Pelayanan Kesehatan Publik melalui Implementasi Aplikasi SiKuat di Puskesmas Kota Sidoarjo - Purwita, Anggraeni Widya; Izzati, Berlian Maulidya; Cinthya, Monica; Elfaiz, Ersha Aisyah; Abdillah, Rifqi (Institut Teknologi Adhi Tama Surabaya, 2025)
Digital transformation is an important part of improving the quality of health services, especially through the implementation of information systems. SiKuat is an information system developed to support the efficiency of the Puskesmas. The purpose of this study is to analyze the implementation process of SiKuat using the Diffusion of Innovation theory as an analytical framework with a qualitative approach with a case study. From the results of interviews, observations, and document analysis, it shows that SiKuat has a relative advantage in accelerating and efficient service time, as well as observability whose benefits are easily observed directly by users, especially during queues and waiting times for services. However, obstacles occur in the aspect of system compatibility with the flow and work procedures that are customary, and the complexity and trial capabilities there is no trial phase before SiKuat is fully implemented during operations because the system is relatively complicated. Without increasing training, adjustment systems, and gradual implementation of strategies, the implementation of SiKuat is at risk of being limited to the initial user group. Strengthening the five innovation attributes in a balanced manner is needed to expand the institutional diffusion system to the early majority phase.